Development of functional bread with beta glucan and black tea and effects on appetite regulation, glucose and insulin responses in healthy volunteers - Abbe Maleyki Mhd Jalil
In the UK, dietry fibre intake is below the recommended level of 30 g/day. The manipulation of behavioural change is challenging, hence finding alternative ways to improve diet is important. The development of functional foods such as bread with added functional ingredients such as B-glucan and black tea may be more feasible and acceptable than changing to a new eating pattern. B-glucan and black tea are often eaten separately, however there maybe a food-matrix interaction between starch, protein (gluten), tea (poly)phenols and B-glucan when added together in a bread. We hypothesise that B-glucan and black tea will be digested slowly and display a blunted postprandial glycaemia. Some undigested residues will reach the colon, where it will be metabolised to short chain fatty acids (SCFA). SCFA, particularly propionate, have the potential to increase satiety by stimulating G protein receptors, however the effects on food intake need to be tested. This project described: i) development of a functional bread containing black tea , BT; B-glucan, BG; B-glucan and black tea, BGBT and compare it to normal white bread (WB) (study 1); ii) determination of bread palatability, perceived satiety and subsequent energy intake following ingestion (study 2); iii) determination of postprandial glucose and insulin responses, and appetite hormones (CCK, PYY and GLP-1) among healthy volunteers (study 3 - in vivo study). In study 1, the breads were developed and tested for starch functionality, antioxidant potential and in vitro fermentability mimicking human colonic fermentation. BG and BGBT breads reduced early (10-min) in vitro starch hydrolysis and this could be due to action of B-glucan that 'protected' some of the starch granules (microscopic study) against amylolysis. Digestion with amylase increased antioxidant potential and total (poly) phenols content of BT and BGBT breads compared with WB. In vitro propionate concentration did not increase significantly when fermented with B-glucan. High inter-individual variation was observed for individual SCFA production. The addition of black tea had no apparent effect on SCFA production. Study 2 is a randomised, crossover study design conducted in healthy volunteers. Breads were given as breakfast and perceived satiety (perceived fullness, hunger, satiety, desire to eat and prospective food intake) was measured postprandially for 3 h. Ad libitum lunch was given after 3 h and energy intake estimated. BT bread was the most acceptable among all breads. BG and BGBT breads showed adverse taste, texture and palatability but showed similar overall acceptability as WB and BT breads. Female subjects showed lower preference for taste, texture and palatability of BG and BGBT compared with WB. BG and BGBT had positive effects on perceived satiety as follows : 1) decreased hunger; 2) increased fullness; and 3) decreased desire to eat. However, eating BG and BGBT at breakfast did not reduce energy intake at lunch compared with WB. Study 3 was similar to study 2. Only BG bread showed significantly lower glucose TAUC0-180 min compared with BT and BGBT but has no apparent effect on insulin response. No significant changes were observed for CCK and GLP-1 responses for all breads. However, BG and BGBT showed lower PYY TAUC0-180 min compared with BT. In vitro starch hydrolysis did not correlate with in vivo postprandial glycaemic responses. In conclusion, these studies suggest that breads with B-glucan and/or black tea have positive effects on perceived satiety in vivo and show good overall acceptability. However, BG and BGBT showed lower PYY TAUC0-180 min compared with BT. In vitro starch hydrolysis did not correlate with in vivo postprandial glycaemic responses. In conclusion, these studies suggest that breads with B-glucan and/or black tea have positive effects on perceived satiety in vivo and show good overall acceptability. However, there is no clear evidence that they affect appetite regulation. Breads containing 7 g B-glucan per 50 g of available carbohydrate reduced in vivo glucose response without altering insulin responses. There was no additional effect of adding black tea together with B-glucan to bread on the in vivo postprandial glycaemic response. It is too early to generalise the results from in vitro batch fermentation and starch hydrolysis and this needs to be considered when planning future dietary interventions looking at both in vitro and in vivo studies. Overall this study concluded that adding soluble dietry fibre to bread is feasible in controlling glycaemic responses and may help increase daily dietry fibre intake.